Display total design sourcebook : 2-D and 3-D design for exhibitions, galleries, museums, and trade shows - Stones, John. (Mies,Switzerland RotoVision, 2008)
All types of exhibition are represented, including permanent, temporary, and traveling shows. The total design of each project is examined, including graphic design, architecture, interiors, lighting, branding, identity, interface design, merchandise, and websites.-- Back cover.
Keywords: Exhibitions -- Design